Sensor network node scheduling for preserving coverage of wireless multimedia networks. (1st October 2019) - Osamy, Walid; Khedr, Ahmed M.; Salim, Ahmed; Agrawal, Dharma P.
Abstract : Wireless multimedia sensor networks (WMSNs) are receiving increasing consideration in the deployment of unmanned surveillance systems for applications such as monitoring battle field and security surveillance. However, ensuring high levels of coverage of the monitored area and concurrently maximising the WMSN lifetime remains a challenging issue. The authors introduce a novel distributed algorithm in this study, for scheduling multimedia sensor nodes (MSNs) activity that maximises coverage and minimises energy consumption. The proposed activity scheduling algorithm incorporates an approach that enables each MSN in WMSN to efficiently extract its cover sets to ensure that the critical points are monitored, and thereby minimise and effectively balance the network energy utilisation. They introduce a new way to select the most suitable cover set of an MSN by assigning priority for each cover set based on the correlation of visual information from the camera observations. The efficacy of the proposed approach is studied through rigorous simulations. Their simulation work and results comparison with existing approaches demonstrate that their proposed scheme exceeds current results in terms of network lifetime, capture rate and percentages of dead and active nodes.